What's Hot in Literacy: New Topics and New Frontiers are Abuzz. Issue 1 (2nd January 2021) - Cassidy, Jack; Ortlieb, Evan; Grote-Garcia, Stephanie
ABSTRACT: The What's Hot in 2019 survey was conducted to measure the amount of attention currently being given to literacy topics in research and practice. Twenty-five literacy leaders were surveyed; results were subsequently categorized into three levels: a) extremely hot or cold, b) very hot or cold, or c) hot or cold This year, there were four topics deemed "very hot": digital/multimodal literacies; disciplinary literacies; early literacy; and English learners/ESL. A current analysis of timely research and practice is provided of both "very hot" topics as well as "should be hot" topics like comprehension, policy and advocacy, struggling readers, and writing. Teachers, administrators, and researchers alike can benefit from staying up to date with hot topics and current issues in literacy; implications for policy and practice regarding literacy instruction and developing the needs of diverse literacy learners are discussed.